InP based quantum dots for long wavelength emissions and their post-growth bandgap tuning - Tang, Xiaohong (2015)
InP based III–V compound semiconductor quantum dot (QD) structures emitting at mid-infrared range were grown by using metal-organic chemical vapor deposition (MOCVD). A two-step growth of QDs method was used to grow the QDs to improve the QDs' shape, dot density and the dot size uniformity. Emission wavelength of the InAs QDs grown on the In xGa1 –xAs matrix layers has been extended to the longest >2.35 μm measured at 77 K. High quality narrower bandgap semiconductor InAsSb QDs have been grown on InP substrate using the alternative interruption-growth method. The emission wavelength of the InAsSb QDs was measured at > 2.8 μm. Selective post-growth band gap tuning of the self-assembly grown InAs/InGaAs/InP QD structure has also been investigated. Very large band gap tuning of over 158 meV has been received by exposing the sample under argon plasma and followed by thermal annealing it at 780 °C. This large selective band gap tuning paves a way for monolithic integration of passive and active devices in QD systems.